Tactics and methods of questioning witnesses in preparatory proceedings - Marcin Kuźmiński (Polish Journal of Social Rehabilitation, 2014)
The author focuses on the activity of witness interrogation during a criminal case. Currently, making statements by a witness is treated as one of the most important parts of the preparatory proceeding. The article presents the ways in which an interrogation should be carried out. The article is based on books and documents deriving from many eminent police officers, public prosecutors and criminologists. The aims of the paper are as follows: outlining the rights and obligations of a witness in a criminal proceeding; description of procedures during questioning; drawing attention do the process of verifying statements.